A wave-transparent self-cleaning coating material, a preparation method and application thereof

CN118420379BActive Publication Date: 2026-10-16HARBIN INST OF TECH AT WEIHAI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410355241.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2026-10-16
Estimated Expiration
2044-03-27

AI Technical Summary

Technical Problem

[0006]采用无机粉料制备锂铝硼硅微晶玻璃防护涂层的传统方法存在各组分材料分散难以达到分子级别分散程度的问题,且由于各组分之间结合程度低,在前期物料混合和后续高温处理下,硼酸,氧化锂等组分会大量挥发,在污染环境的同时还提高了成本;同时,传统无机浆料的渗透能力和流动能力差,其与复合材料表面间由于结合紧密度差,不可避免地存在空隙,影响防护性能;再者,传统方法防护机理单一,在玻璃涂层形成前的阶段内,不具备相应的防水性能,不能实现在实际应用中全阶段防护

Benefits of technology

[0064] This invention employs an organosilicon-inorganic hybrid encapsulation network to improve the uniformity of the material system and enhance the coating performance of the coating slurry on the substrate surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118420379B_ABST
    Figure CN118420379B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of rain erosion resistance and waterproof, and relates to a wave-transparent self-cleaning coating material and a preparation method and application thereof. The wave-transparent self-cleaning coating material is prepared from a boron-aluminum-silicon-lithium sol and a hydroxyl silicone oil. After ball milling treatment and drying, the wave-transparent self-cleaning material is coated on the surface of a substrate, and the substrate is heat treated to obtain a silicone hydrophobic coating, and the heat treatment is continued to obtain a microcrystalline glass hydrophilic coating. The coating is prepared by using an organic precursor method, the mixing uniformity of raw materials is improved, molecular-level diffusion is achieved, the coating performance on the surface of the substrate is improved, the silicone hydrophobic coating has waterproof performance, and after the heat treatment is continued, the generated microcrystalline glass hydrophilic coating is an inorganic waterproof wave-transparent coating. The coating not only has rain erosion resistance, but also can realize self-cleaning. The two coatings can realize multi-temperature-stage protection of the substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wave-transparent coating materials technology, and more specifically relates to a wave-transparent self-cleaning coating material, its preparation method and application. Background Technology

[0002] Quartz fiber reinforced quartz ceramic matrix composites not only have excellent properties such as low density, good mechanical properties, high temperature resistance, and ablation resistance, but also have good wave transmission properties. They are excellent materials for antenna windows, which can avoid the instability of antenna signal reception caused by external environmental interference. They are very important structural components in aerospace and deep-sea exploration fields.

[0003] However, the composite material has high porosity and high surface energy. In humid environments such as rain, smog, and seawater immersion, the intrusion of water, a high-loss medium for electromagnetic waves, not only leads to a serious decrease in wave transmission performance, but also causes a significant reduction in the durability of the material, which in turn seriously affects the service life of the antenna window and the accuracy of the antenna signal reception.

[0004] To address the aforementioned issues, extensive research has been conducted on the protection of antenna window materials. Among these, lithium aluminum silicon glass-ceramic systems have attracted considerable attention due to their excellent thermal properties (such as extremely low coefficient of thermal expansion and high thermal shock resistance), low density, good wave transmission performance, and excellent water resistance. By adjusting the proportions of the components in the lithium aluminum silicon glass system or adding a small amount of nucleating agent, researchers can obtain glass-ceramic materials with different crystalline phases and degrees of crystallinity under different heat treatment processes.

[0005] Boron oxide, as a glass network forger, when introduced into the lithium aluminum borosilicate glass (LAB) microcrystalline glass system, participates in network formation, connecting breakpoints in the glass network and increasing its density. Simultaneously, it lowers the glass transition temperature of the system. The LAB microcrystalline glass system can achieve low-temperature, extremely low-energy production of microcrystalline glass; furthermore, by controlling the heat treatment process and the proportions of each component, its surface hydrophilicity and hydrophobicity can be adjusted.

[0006] Traditional methods for preparing lithium aluminum borosilicate microcrystalline glass protective coatings using inorganic powders suffer from several drawbacks. Firstly, the dispersion of individual components is difficult to achieve at the molecular level. Secondly, due to the low bonding strength between components, boric acid, lithium oxide, and other components volatilize significantly during initial material mixing and subsequent high-temperature treatment, polluting the environment and increasing costs. Thirdly, traditional inorganic slurries have poor penetration and flowability, resulting in unavoidable voids between them and the composite material surface due to poor bonding tightness, thus affecting protective performance. Furthermore, traditional methods have a single protective mechanism and lack adequate waterproofing properties before the glass coating forms, failing to provide comprehensive protection throughout the entire application process.

[0007] Therefore, how to provide a wave-transparent coating that is environmentally friendly in the production process, has multi-temperature range and multi-mechanism protection, high temperature resistance, strong rain erosion resistance and durability, and can achieve self-cleaning is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0008] To address the aforementioned technical problems, this invention provides a microwave-transparent self-cleaning coating material, its preparation method, and its application. The prepared boron-aluminum-silicon-lithium sol exhibits good uniformity, high purity, controllable microscopic sol particle morphology, and a unique microstructure. Furthermore, it possesses stable physical and chemical properties. The microwave-transparent self-cleaning coating material is prepared by reacting the boron-aluminum-silicon-lithium sol with hydroxyl silicone oil. The further prepared coating exhibits multi-temperature range protection, high temperature resistance, strong rain erosion resistance, and self-cleaning characteristics. Moreover, the production process of the coating material is environmentally friendly.

[0009] To achieve the above objectives, the present invention provides the following technical solution:

[0010] One of the technical solutions of this invention is to provide a method for preparing boron-aluminum-silicon-lithium sol, comprising:

[0011] The lithium precursor is added to the boron-aluminum-silicon sol and subjected to a hydrothermal reaction under stirring conditions to obtain the boron-aluminum-silicon-lithium sol.

[0012] The lithium precursor is lithium hydroxide or a lithium-containing alkoxide.

[0013] Furthermore, the mass ratio of the boron-aluminum-silicon sol to the lithium precursor is 5:2.

[0014] The boron-aluminum-silicon-lithium sol prepared under the specified raw material ratios in this invention exhibits a high degree of amorphization and a more stable three-dimensional network structure compared to most other boron-aluminum-silicon-lithium sols prepared with different ratios, while also having lower material costs. When the specified ratios are exceeded, i.e., the proportion of lithium hydroxide or lithium alkoxides is too low, the three-dimensional network structure of the sol becomes unstable due to the lack of lithium ions; if the proportion is too high, the excess lithium ions will react to form a crystalline phase, destroying the sol structure and thus affecting the chemical activity of the sol.

[0015] Furthermore, the lithium-containing alkoxide includes one of lithium methoxide, lithium ethanol, and lithium isopropoxide.

[0016] This invention uses lithium hydroxide or lithium-containing alkoxides to prepare the sol, which allows lithium ions to be uniformly dispersed in the sol; it also avoids introducing new inorganic impurity ions, resulting in a high-purity sol; and the chemical composition ratio is easy to achieve and adjustable. If inorganic lithium salts are used to prepare boron-aluminum-silicon-lithium sol, inorganic impurity ions will be introduced, reducing the purity of the sol and even causing side reactions.

[0017] Furthermore, the stirring speed is 200-300 rpm.

[0018] Furthermore, the hydrothermal reaction is carried out at a temperature of 80°C for 4 hours.

[0019] Under the hydrothermal reaction conditions (temperature and time) defined in this invention, the reaction is more likely to proceed fully and stably, resulting in a high-quality boron-aluminum-silicon-lithium sol.

[0020] Furthermore, both the stirring and the hydrothermal reaction are carried out under closed conditions.

[0021] Lithium hydroxide or lithium alkoxides are hygroscopic. A sealed environment prevents moisture from entering the mixture, ensuring the reaction proceeds normally and preventing harmful substances produced from escaping and polluting the environment. Non-sealed environments will cause the aforementioned problems.

[0022] Furthermore, the preparation method of the boron-aluminum-silica sol includes the following steps:

[0023] The boron-aluminum-silica sol is obtained by dissolving aluminum alkoxides and siloxanes in an aqueous solution of boron oxide or boron alkoxides and then subjecting the solution to a hydrothermal reaction under stirring conditions.

[0024] Preferably, the mass ratio of the aluminum alkoxide, siloxane, and boron oxide or boron alkoxide is 1:3:4.

[0025] The boron-aluminum-silica sol obtained under the raw material ratio conditions specified in this invention has a stable microstructure and higher chemical activity than sols prepared under most other ratio conditions, and the material cost is lower. When the ratio is exceeded, the structural atoms that should form a three-dimensional network structure of the sol will react to form a crystal phase and destroy the three-dimensional structure, thereby affecting the chemical activity of the sol.

[0026] Preferably, the aluminum alkoxide includes one of aluminum isopropoxide, aluminum n-propoxide, and aluminum n-butoxide.

[0027] Preferably, the siloxane includes one of trimethylethoxysilane, cyclobutyroxysilane, and propylsiloxane.

[0028] Preferably, the boron-containing alkoxide includes one of lithium tetraborate, methanol boric acid, and tris(trimethylsilyl)borate.

[0029] Sols prepared using metal alkoxides have the advantages of low preparation temperatures, high purity, and molecular-level dispersion uniformity. The chemical composition is easily achievable and adjustable. Most importantly, the molecular structure can be designed by controlling the hydrolysis-condensation process of the metal alkoxides. In contrast, using other raw materials such as inorganic salts to prepare sols makes the reaction process difficult to control, the chemical composition is not adjustable, and therefore, it is more difficult to obtain the desired product compared to using metal alkoxides. Furthermore, the dispersion uniformity of the resulting sol is far inferior to that of gels prepared using metal alkoxides.

[0030] Preferably, the mass concentration of boron in the boron oxide or boron-containing alkoxide aqueous solution is 20–40 wt.%.

[0031] The concentration of boron oxide or boron-containing alkoxide aqueous solution selected in this invention ensures sufficient boron oxide molecules in the sol, thereby giving the sol network structure good stability. If the concentration is too low, the resulting sol network structure will be unstable and chemically inactive; if the concentration is too high, the excess boron oxide will have no significant effect on the sol network structure, increasing costs and wasting raw materials.

[0032] Preferably, both the stirring and the hydrothermal reaction are carried out under closed conditions.

[0033] Preferably, the hydrothermal reaction is carried out at a temperature of 70°C for 4 hours.

[0034] The hydrothermal parameters specified in this invention facilitate rapid and stable reaction, ensuring completeness and yielding a reliable and effective boron-aluminum-silica sol. Too low a temperature or too short a time will result in incomplete reaction, low sol production efficiency, or even no reaction at all; too high a temperature or too long a time will cause side reactions, leading to a decrease in sol yield.

[0035] Preferably, the stirring speed is 200-300 rpm.

[0036] The second technical solution of the present invention provides a boron-aluminum-silicon-lithium sol prepared by the above preparation method.

[0037] The third technical solution of the present invention provides a wave-transparent self-cleaning coating material, the raw materials of which include 30-50 parts of the above-mentioned boron aluminum silicon lithium sol and 40-60 parts of hydroxyl silicone oil.

[0038] The beneficial effects of the above scheme are as follows: hydroxyl silicone oil has good temperature resistance, is resistant to dilution, is not easily volatile, and is harmless to the environment and human body. Most importantly, it can react with the chemical bonds in boron-aluminum-silicon-lithium sol to form cross-linked products, thereby introducing silicon elements. Other silicone oils or silicon-containing compounds cannot react and combine well with the components of boron-aluminum-silicon-lithium sol, making it difficult to introduce silicon elements into the sol network structure, or even destroying the sol network structure, thus failing to obtain the above coating material.

[0039] With this raw material ratio, the proportion of hydroxyl silicone oil is slightly larger, which ensures the completeness of the reaction and maximizes the introduction of silicon elements without wasting raw materials, thus obtaining high-quality microwave-transparent self-cleaning materials.

[0040] Fourth technical solution of the present invention: A method for preparing a wave-transparent self-cleaning coating material, comprising the following steps:

[0041] Hydroxyl silicone oil is added to boron aluminum silicon lithium sol, and the mixture undergoes a hydrothermal reaction under stirring conditions to obtain the wave-transparent self-cleaning coating material.

[0042] Furthermore, the stirring speed is 200-300 rpm.

[0043] Furthermore, the hydrothermal reaction temperature is 80°C and the time is 4 hours.

[0044] Furthermore, both the stirring and the hydrothermal reaction are carried out under closed conditions.

[0045] The beneficial effects of the above-mentioned further scheme are: these hydrothermal parameters facilitate a rapid and stable reaction, ensuring its completeness and resulting in a high-quality, microwave-transparent, self-cleaning coating material. Too low a temperature or too short a time will lead to an incomplete reaction, resulting in low coating material production efficiency, or even no reaction at all, making it impossible to obtain the coating material. Too high a temperature or too long a time will cause side reactions, leading to a decrease in the yield and quality of the coating material.

[0046] Fifth technical solution of the present invention: to provide an application of the above-mentioned wave-transparent self-cleaning material in an organosilicon hydrophobic coating or a microcrystalline glass hydrophilic coating.

[0047] The sixth technical solution of this invention: provides a method for preparing an organosilicon hydrophobic coating containing the above-mentioned wave-transparent self-cleaning material, comprising the following steps:

[0048] The microwave-transparent self-cleaning material was ball-milled and then dried to obtain a slurry.

[0049] The slurry is coated onto the surface of the material and then heat-treated to obtain an organosilicon hydrophobic coating.

[0050] Furthermore, the ball milling is performed at room temperature for 1 to 3 hours.

[0051] Furthermore, the drying temperature is 40–80°C.

[0052] Furthermore, the water content of the slurry is 5%.

[0053] Furthermore, the heat treatment temperature is 200℃, the heating rate is 5~8℃ / min, and the holding time is 1h.

[0054] The seventh technical solution of this invention: provides a method for preparing a hydrophilic coating on microcrystalline glass, comprising:

[0055] The above-mentioned organosilicon hydrophobic coating is subjected to heat treatment to obtain the microcrystalline glass hydrophilic coating.

[0056] Furthermore, the heat treatment temperature is 700℃, the heating rate is 5-8℃ / min, and the holding time is 1h.

[0057] The eighth technical solution of the present invention provides a coating prepared according to the preparation method of organosilicon hydrophobic coating or the preparation method of microcrystalline glass hydrophilic coating.

[0058] It is worth noting that:

[0059] The hydrophilic coating of the microcrystalline glass formed in this invention is mainly composed of spodumene solid solution as the main crystalline phase. During the heat treatment process, phase separation first occurs in the glass matrix, and many nanoscale droplets appear in the disordered glass mass. At the interface between the droplets and the glass matrix, a large number of crystal nucleation sites are generated. The spodumene solid solution continuously deposits and grows on the surface of the crystal nuclei, and its growth rate and quantity are affected by the heat treatment temperature and time, as well as the raw material ratio.

[0060] In the initial stage of crystal formation, due to the difference in thermal expansion coefficients between the crystal and the matrix, cracks and opacity are easily generated in the glass system. Subsequently, the tiny initial spodumene crystals gradually grow by absorbing the silica-rich components in the molten glass, forming a gradient shell. This gradually reduces the difference in physicochemical properties between the crystal and the matrix, thereby enhancing the glass's transparency and resistance to crack propagation.

[0061] In the spatial network formed by the stacking and interconnection of silicon-oxygen tetrahedra, aluminum atoms can enter the network through tetracoordination with oxygen atoms, partially replacing silicon atoms. This causes distortion of the original silicon-oxygen network lattice, producing a strengthening effect while also creating porosity. At this point, lithium ions, acting as cationic ligands, coordinate with the negatively charged aluminum-oxygen tetrahedra, maintaining the electrical neutrality of the glass network. Simultaneously, the presence of lithium ions disrupts the regular structure of the glass network to some extent, enhancing the crystallization ability of the glass system.

[0062] Ultimately, β-spodumene was formed during the heat treatment process. Spodumene undergoes transformations at different temperatures, forming α-spodumene, β-spodumene, and γ-spodumene crystal phases. After high-temperature treatment, the spodumene solid solution mainly exists stably in the tetragonal β-spodumene, i.e., K-quartz. Due to the in-situ precipitation of fine grains with ultra-low thermal expansion coefficients, a grain refinement strengthening effect is ultimately produced, which greatly improves the hardness, compressive strength, and shear strength of the glass matrix, thereby enhancing the durability of the glass-ceramic.

[0063] As can be seen from the above technical solution, compared with the existing technology, it has the following beneficial effects:

[0064] This invention employs an organosilicon-inorganic hybrid encapsulation network to improve the uniformity of the material system and enhance the coating performance of the coating slurry on the substrate surface.

[0065] This invention employs an organic precursor method to prepare the coating, improving the uniformity of raw material mixing and achieving molecular-level diffusion. This enhances the coating's adhesion to the substrate surface. The initially obtained organosilicon coating exhibits waterproof properties, and after further heat treatment, the waterproofing mechanism transforms, resulting in a microcrystalline glass coating that is an inorganic waterproof and wave-transparent coating. This provides multi-temperature protection, exhibiting not only rain erosion resistance but also self-cleaning capabilities. The coating provided by this invention can be effectively applied in practical work within the field of wave-transparent, rain-erosion-resistant, and self-cleaning coating materials, meeting the waterproofing requirements of substrate materials.

[0066] The preparation process of the lithium aluminum borosilicate microwave-transparent hydrophilic microcrystalline glass coating provided by this invention has good repeatability, low cost, no harmful substances are volatilized during the preparation process, it is environmentally friendly, clean and non-toxic, and easy to mass-produce. Attached Figure Description

[0067] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings:

[0068] Figure 1 The image shows the infrared spectrum of the slurry prepared in Example 1.

[0069] Figure 2 The infrared spectrum of the microcrystalline glass prepared in Example 2 is shown.

[0070] Figure 3 The images show the surface microstructures of the glass-ceramic prepared for comparative examples 1 to 4, where (a) is comparative example 1, (b) is comparative example 2, (c) is comparative example 3, and (d) is comparative example 4.

[0071] Figure 4 The images show the surface microstructures of the glass-ceramic prepared for comparative examples 5 to 8, where (a) is comparative example 5, (b) is comparative example 6, (c) is comparative example 7, and (d) is comparative example 8.

[0072] Figure 5 The diagram illustrates the waterproofing principle of a microcrystalline glass coating, where (a) no microcrystalline glass coating is applied, (b) the surface microcrystalline glass coating is incomplete, and (c) the surface microcrystalline glass coating is smooth and dense. Detailed Implementation

[0073] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0074] The room temperature in this invention refers to 25±2℃.

[0075] The trimethylethoxysilane, boron oxide, glacial acetic acid, aluminum isopropoxide, hydroxyl silicone oil, carboxylated silicone oil, and lithium hydroxide used in this invention are all commercially available analytical grade products.

[0076] The substrate in this embodiment of the invention is a quartz fiber reinforced quartz ceramic matrix composite material. The composite material was purchased from Shandong Institute of Arts and Crafts Ceramics. The specifications are 30mm*30mm*5mm (area is 30mm*30mm, thickness is 5mm). The real part of the dielectric constant is 3.1 and the dielectric loss tangent is 0.010, as determined by the waveguide method.

[0077] Example 1

[0078] Preparation of organosilicon hydrophobic coating:

[0079] 1) Heat 500g of water to 50℃, add 40g of boron oxide, then add 30g of trimethylethoxysilane and 10g of aluminum isopropoxide dropwise, raise the temperature to 70℃, use hydrochloric acid to adjust the pH value to 3 to promote the hydrolysis of trimethylethoxysilane and aluminum isopropoxide, and perform hydrothermal treatment at 70℃ for 4 hours in a closed environment while stirring to obtain a transparent gel-like boron aluminum silicate sol.

[0080] 2) Add 10g of lithium hydroxide to 300g of water, dissolve it, and then add it to 25g of the boron-aluminum-silica sol prepared in step 1). Under 80℃ conditions, perform hydrothermal treatment in a closed environment for 4 hours while heating and stirring to obtain a transparent gel-like boron-lithium-aluminum-silica sol.

[0081] 3) The boron aluminum silicon lithium sol and hydroxyl silicone oil are mixed at a mass ratio of 3:4 and subjected to a closed hydrothermal treatment at 80°C for 4 hours while being heated and stirred to obtain a wave-transparent self-cleaning coating material.

[0082] 4) The microwave-transparent self-cleaning coating material was added to a ball mill and ball-milled for 3 hours at room temperature to obtain the precursor of the organosilicon-inorganic hybrid encapsulation system;

[0083] 5) The precursor was placed in an oven and dried at 60°C to obtain a slurry with a water content of 5%;

[0084] 6) The slurry is coated onto the surface of the quartz fiber reinforced quartz ceramic matrix matrix using a scraping method, with a coating thickness of 1 mm;

[0085] 7) The composite material coated with slurry is placed in a three-phase resistance furnace and heated to 200℃ for 1 hour in air atmosphere at a heating rate of 5℃ / min to obtain a smooth and opaque organosilicon hydrophobic coating.

[0086] The wetting angle of the silicone hydrophobic coating was measured to be 154° and the roll-off angle to be 8.9° using a drop contact angle meter. After 8 days of damp heat cycling at 98% humidity and 30°C, the moisture absorption rate was 0.032%.

[0087] The wave transmission performance of the organosilicon hydrophobic coating was determined by waveguide method. The real part of the dielectric constant was 3.3, and the dielectric loss tangent was 0.021.

[0088] Example 2

[0089] Preparation of hydrophilic coatings for microcrystalline glass:

[0090] In a three-phase resistance furnace under an air atmosphere, the organosilicon hydrophobic coating prepared in Example 2 was heated to 700°C at a heating rate of 5°C / min and held for 1 hour to obtain a smooth and transparent microcrystalline glass hydrophilic coating.

[0091] The wetting angle of the microcrystalline glass hydrophilic coating was less than 5° as measured by a drop contact angle meter. After immersion in water at room temperature for 72 hours, the moisture absorption rate was 0.043%. After 8 days of damp heat cycling at 98% humidity and 30°C, the moisture absorption rate was 0.022%.

[0092] The wave transmission performance of the hydrophilic coating of the microcrystalline glass was determined by waveguide method. The real part of the dielectric constant was 3.2 and the dielectric loss tangent was 0.019.

[0093] The hardness of the microcrystalline glass hydrophilic coating was measured to be 9H using a pencil hardness test.

[0094] The adhesion of the microcrystalline glass hydrophilic coating was rated as level 1 by the cross-cut adhesion test.

[0095] The shear strength of the microcrystalline glass hydrophilic coating was determined to be 11 MPa using a universal mechanical testing machine.

[0096] Example 3

[0097] Preparation of organosilicon hydrophobic coating:

[0098] 1) Heat 500g of water to 50℃, add 40g of boron oxide, then add 30g of trimethylethoxysilane and 10g of aluminum isopropoxide dropwise, raise the temperature to 70℃, use hydrochloric acid to adjust the pH value to 3 to promote the hydrolysis of trimethylethoxysilane and aluminum isopropoxide, and perform hydrothermal treatment at 70℃ for 4 hours in a closed environment while stirring to obtain a transparent gel-like boron aluminum silicate sol.

[0099] 2) Add 10g of lithium hydroxide to 300g of water, dissolve it, and then add it to 25g of boron-aluminum-silica sol prepared in Example 1. Under 80°C, perform hydrothermal treatment in a closed environment for 4 hours while heating and stirring to obtain a transparent gel-like boron-lithium-aluminum-silica sol.

[0100] 3) The boron aluminum silicon lithium sol and hydroxyl silicone oil are mixed at a mass ratio of 3:4 and subjected to a closed hydrothermal treatment at 80°C for 4 hours while being heated and stirred to obtain a wave-transparent self-cleaning coating material.

[0101] 4) The microwave-transparent self-cleaning coating material is added to a ball mill and ball-milled for 1 hour at room temperature to obtain the precursor of the organosilicon-inorganic hybrid encapsulation system;

[0102] 5) The precursor mixture was placed in an oven and dried at 40°C to obtain a slurry with a water content of 5%;

[0103] 6) The slurry was coated onto the surface of the quartz fiber reinforced quartz ceramic matrix matrix using a scraping method, with a coating amount of 3g;

[0104] 7) The composite material coated with slurry is placed in a three-phase resistance furnace and heated to 200℃ at a heating rate of 6℃ / min under air atmosphere and held for 1h to obtain a smooth and opaque organosilicon hydrophobic coating.

[0105] The wetting angle of the silicone hydrophobic coating was measured to be 154° and the roll-off angle to be 8.7° using a drop contact angle meter. After 8 days of damp heat cycling at 98% humidity and 30°C, the moisture absorption rate was 0.031%.

[0106] The wave transmission performance of the organosilicon hydrophobic coating was determined by waveguide method. The real part of the dielectric constant was 3.3 and the dielectric loss tangent was 0.014.

[0107] Example 4

[0108] Preparation of hydrophilic coatings for microcrystalline glass:

[0109] In a three-phase resistance furnace under an air atmosphere, the organosilicon hydrophobic coating prepared in Example 3 was heated to 700°C at a heating rate of 6°C / min and held for 1 hour to obtain a smooth and transparent microcrystalline glass hydrophilic coating.

[0110] The wetting angle of the microcrystalline glass hydrophilic coating was measured to be 4.3° using a drop contact angle meter. After immersion in water at room temperature for 72 hours, the moisture absorption rate was 0.041%. After 8 days of damp heat cycling at 98% humidity and 30°C, the moisture absorption rate was 0.024%.

[0111] The wave transmission performance of the hydrophilic coating of the microcrystalline glass was determined by waveguide method. The real part of the dielectric constant was 3.4, and the dielectric loss tangent was 0.012.

[0112] The hardness of the microcrystalline glass hydrophilic coating was measured to be 9H using a pencil hardness test.

[0113] The adhesion of the microcrystalline glass hydrophilic coating was rated as level 1 by the cross-cut adhesion test.

[0114] The shear strength of the microcrystalline glass hydrophilic coating was determined to be 10.1 MPa using a universal mechanical testing machine.

[0115] Example 5

[0116] Preparation of organosilicon hydrophobic coating:

[0117] Same as Example 1, except that the drying temperature in step 5) is 80°C.

[0118] The increased drying temperature accelerates the pre-crosslinking rate and dehydration rate of the slurry coating, resulting in reduced moisture content during subsequent heat treatment, improved coating uniformity and density. After 8 days of wet heat cycling at 98% humidity and 30°C, the moisture absorption rate is 0.030%.

[0119] Comparative Example 1

[0120] Preparation of organosilicon hydrophobic coating:

[0121] Same as Example 1, except that the drying temperature in step 5) is 30°C.

[0122] The reduced drying temperature slowed down the pre-crosslinking and dehydration rates of the slurry coating, leading to an increase in moisture content during subsequent heat treatment. This resulted in porosity within the coating, reducing its density. After 8 days of damp heat cycling at 98% humidity and 30°C, the moisture absorption rate was 0.035%. The real part of the dielectric constant was 2.9, and the dielectric loss tangent was 0.012.

[0123] Comparative Example 2

[0124] Preparation of organosilicon hydrophobic coating:

[0125] Same as Example 1, except that the heating rate in step 7) is 10°C / min.

[0126] Due to the increased heating rate, the silicone coating dehydrated too quickly, resulting in localized over-crosslinking, increased uneven shrinkage of the coating, and decreased surface smoothness. The moisture absorption rate was 0.044% after 8 days at 98% humidity and 30°C. The surface wetting angle was 145°, and the roll-off angle was 14.3°.

[0127] Comparative Example 3

[0128] Preparation of organosilicon hydrophobic coating:

[0129] Compared with Example 1, the difference is that in step 7), the temperature is increased to 150°C at a heating rate of 5°C / min.

[0130] Due to the reduced heating temperature, the degree of cross-linking of the coating decreased, resulting in a lower density. After 8 days of damp heat cycling at 98% humidity and 30°C, the moisture absorption rate was 0.036%. The real part of the dielectric constant was 2.7, and the dielectric loss tangent was 0.011.

[0131] Comparative Example 4

[0132] Preparation of organosilicon hydrophobic coating:

[0133] Compared with Example 1, the difference is that in step 7), the temperature is increased to 220°C at a heating rate of 5°C / min.

[0134] Due to the increased heating temperature, the degree of cross-linking and density of the coating are improved. After 8 days of damp heat cycling at 98% humidity and 30°C, the moisture absorption rate is 0.029%. The real part of the dielectric constant is 3.6, and the dielectric loss tangent is 0.025.

[0135] Comparative Example 5

[0136] Preparation of hydrophilic coatings for microcrystalline glass:

[0137] The difference from Example 2 is that the temperature was increased to 700°C at a heating rate of 10°C / min.

[0138] The increased heating rate caused the silicone hydrophobic coating to decompose too quickly, resulting in insufficient diffusion of bubbles inside the microcrystalline glass, uneven diffusion of substances within the glass system, reduced crystal nuclei formation, and decreased glass density. The moisture absorption rate was 0.045% after immersion in water at room temperature for 72 hours, and 0.031% at 98% humidity and 30 degrees Celsius. The hardness was 9H, the adhesion was grade 1, and the shear strength was 8.1 MPa.

[0139] Comparative Example 6

[0140] Preparation of hydrophilic coatings for microcrystalline glass:

[0141] Compared with Example 2, the difference is that the temperature is increased to 700°C at a heating rate of 3°C / min.

[0142] Due to the reduced heating rate, the internal material diffuses more fully, the amount of crystal nuclei formed increases, the glass is fully vented, the density is improved, the moisture absorption rate is 0.040% after immersion in water at room temperature for 72 hours, the moisture absorption rate is 0.021% after 8 days of wet heat cycling at 30℃ and 98% humidity, the hardness is 9H, the adhesion is grade 1, and the shear strength is 12MPa.

[0143] Comparative Example 7

[0144] Preparation of hydrophilic coatings for microcrystalline glass:

[0145] The difference from Example 2 is that the temperature was increased to 680°C at a heating rate of 5°C / min.

[0146] Due to the reduced heating temperature, the internal density of the coating decreased, the amount of crystal nuclei formed was reduced, the hardness was 9H, the adhesion was grade 1, and the shear strength was 7.9MPa.

[0147] Comparative Example 8

[0148] Preparation of hydrophilic coatings for microcrystalline glass:

[0149] Compared with Example 2, the difference is that the temperature is increased to 800°C at a heating rate of 5°C / min.

[0150] Due to the increased heating temperature, the overall mechanical properties of the composite material deteriorated, the amount of glass coating penetrating into the matrix increased, the amount of residual glass phase on the surface decreased, the hardness was 8H, the adhesion was grade 1, and the shear strength was 7.1 MPa.

[0151] Comparative Example 9

[0152] Preparation of organosilicon hydrophobic coating:

[0153] Same as Example 1, except that the amount of boron oxide added in step 1) is 50g.

[0154] Due to the increased proportion of boron oxide, excessive borides form crystalline phases, which disrupt the network structure of boron-aluminum-silica sol, affecting the network structure of subsequent materials, reducing the glass-forming performance of the coating, decreasing the yield of glass coatings, reducing surface smoothness, and resulting in a surface wetting angle of 136° and a roll-off angle of 20.2°.

[0155] Comparative Example 10

[0156] Preparation of organosilicon hydrophobic coating:

[0157] Same as Example 1, except that the boron aluminum silica sol content in step 2) is 20g.

[0158] Due to the increased proportion of lithium hydroxide, excess lithium ions cannot be embedded into the boron-aluminum-silicon sol network, leading to cation enrichment. These cations then precipitate with silicon or boron elements in the network structure, damaging the boron-aluminum-silicon-lithium network structure. This affects the network structure of subsequent materials, reduces the glass-forming properties of the coating, decreases the glass coating, reduces surface smoothness, and results in a surface wetting angle of 133° and a roll-off angle of 21.3°.

[0159] Comparative Example 11

[0160] Preparation of organosilicon hydrophobic coating:

[0161] Same as Example 1, except that in step 2), hydrothermal treatment is performed at 70°C.

[0162] As the hydrothermal temperature was lowered, the degree of bonding between the various structures in the boron-aluminum-silicon sol decreased, and the chemical activity decreased, which led to a decrease in the stability of the three-dimensional network structure of the subsequently prepared boron-aluminum-silicon-lithium sol, a decrease in the glass-forming properties of the coating, a reduction in the glass coating, a decrease in surface smoothness, a surface wetting angle of 143°, and a roll-off angle of 15°.

[0163] Comparative Example 12

[0164] Preparation of organosilicon hydrophobic coating:

[0165] Same as Example 1, except that in step 3), hydrothermal treatment is performed at 70°C.

[0166] Due to the reduction in hydrothermal temperature, the degree of crosslinking between boron aluminum silica sol and hydroxyl silicone oil decreased, resulting in a decrease in the stability of the three-dimensional network structure of the prepared boron aluminum silica lithium sol, a decrease in the glass-forming properties of the coating, a reduction in the amount of glass coating, a decrease in surface smoothness, a surface wetting angle of 144°, and a roll-off angle of 14.1°.

[0167] Comparative Example 13

[0168] Preparation of organosilicon hydrophobic coating:

[0169] Same as Example 1, except that in step 3), boron aluminum silicon lithium sol and hydroxyl silicone oil are mixed in a mass ratio of 1:1.

[0170] Due to the decrease in the proportion of hydroxyl silicone oil and the reduction in the amount of silicon introduced, the content of silicon-oxygen tetrahedra, which are the main components in the three-dimensional network structure of boron-aluminum-silicon-lithium sol, decreases. The remaining boron-oxygen trigonometric, tetrahedral, and aluminum-oxygen tetrahedra cannot participate in the construction of the three-dimensional network structure, which in turn reduces the content of the boron-aluminum-silicon-lithium three-dimensional network structure, reduces the glass-forming performance of the coating, reduces the amount of glass coating, reduces the surface smoothness, and results in a surface wetting angle of 139° and a roll-off angle of 13.8°.

[0171] Comparative Example 14

[0172] Preparation of organosilicon hydrophobic coating:

[0173] Same as Example 1, except that in step 3), hydroxyl silicone oil is replaced with methyl silicone oil.

[0174] Because methyl silicone oil lacks hydroxyl groups and does not contain silicon-oxygen tetrahedra, it cannot introduce silicon-oxygen tetrahedra to participate in the construction of the boron-aluminum-silicon-lithium network. As a result, the chemical activity of the coating material decreases, the glass-forming performance decreases, the glass coating is reduced, the surface smoothness decreases, the surface wetting angle is 127°, and the roll-off angle is 30.1°.

[0175] Figure 1 The infrared spectrum of the slurry prepared in Example 1 is shown below. Figure 1 It can be seen that the wavenumber is between 500-600 cm⁻¹-1 The peaks at 650-750 cm⁻¹ represent the bending vibration absorption peaks of the Si-O groups in the silicon-oxygen tetrahedron and the asymmetric bending vibration peaks of Si-O-Al, indicating that aluminum-oxygen tetrahedra enter a three-dimensional network dominated by silicon-oxygen tetrahedra, thus forming a network structure with alternating Si-O-Al bonds; the wavenumbers are in the range of 650-750 cm⁻¹. -1 The BO-Si stretching vibration peak and wavenumber at 750–1000 cm⁻¹ are located at this location. -1 The stretching vibration peak of BO-Si at [location] indicates that boron-oxygen trigonometric bodies and boron-oxygen tetrahedra have entered the three-dimensional network containing silicon-oxygen tetrahedra, thus forming a network structure of alternating BO-Si bonds; the wavenumber is at 1000 cm⁻¹. -1 The stretching vibration peak at the main chain Si-O-Si indicates the existence of a silicon-oxygen tetrahedral network structure, and the three-dimensional network is mainly composed of silicon-oxygen tetrahedra. The stretching vibration peak containing organic groups indicates that the slurry composition contains organic groups.

[0176] Figure 2 The infrared spectrum of the microcrystalline glass prepared in Example 2 is shown below. Figure 2 It can be seen that the wavenumber is between 400 and 500 cm⁻¹ -1 The presence of nearby Si-O-Si bending vibration peaks and Si-O-Al asymmetric bending vibration peaks indicates that the prepared glass-ceramic still possesses a network structure of alternating Si-O-Al bonds; the wavenumber is at 1100 cm⁻¹. -1 The nearby Si-OB stretching vibration peaks indicate that most of the silicon-oxygen tetrahedra in the original slurry were combined with boron-oxygen tetrahedra to form an alternating Si-OB network structure; while other peaks indicate the presence of boron-oxygen triangular prisms, tetrahedra, and aluminum-oxygen tetrahedra; and Figure 1 compared to, Figure 2 The absence of absorption peaks containing organic groups indicates that the prepared microcrystalline glass no longer contains organic components.

[0177] Figure 3 The images show the surface microstructures of the glass-ceramics prepared in Comparative Examples 1–4, where (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Comparative Example 3, and (d) is Comparative Example 4. Figure 3 It can be seen that the microcrystalline glass prepared in Comparative Examples 1 to 3 has pores on its surface and even cracks, indicating a decrease in density and surface smoothness. In contrast, the microcrystalline glass prepared in Comparative Example 4 has a smooth surface without pores, indicating that the density has been improved to a certain extent.

[0178] Figure 4 The images show the surface microstructures of the glass-ceramics prepared in Comparative Examples 5–8, where (a) is Comparative Example 5, (b) is Comparative Example 6, (c) is Comparative Example 7, and (d) is Comparative Example 8. Figure 4It can be seen that the microcrystalline glass prepared in Comparative Examples 5 and 7 has micropores on its surface, and its density is reduced compared with the microcrystalline glass prepared in the examples. The microcrystalline glass prepared in Comparative Example 8 has microcracks on its surface, which is the result of the increased amount of glass coating penetrating into the matrix, further proving the reduction of residual glass phase. The microcrystalline glass prepared in Comparative Example 6 has a smooth and flat surface without pores, indicating that its density is improved.

[0179] Figure 5 The diagram illustrates the waterproofing principle of a microcrystalline glass coating, where (a) no microcrystalline glass coating is applied, (b) the surface microcrystalline glass coating is incomplete, and (c) the surface microcrystalline glass coating is smooth and dense.

[0180] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0181] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A wave-transparent self-cleaning coating material, characterized in that, By weight, the raw materials include 30-50 parts boron-aluminum-silicon-lithium sol and 40-60 parts hydroxyl silicone oil; The preparation steps of the boron-aluminum-silicon-lithium sol include: adding a lithium precursor to the boron-aluminum-silicon sol and performing a hydrothermal reaction under stirring conditions to obtain the boron-aluminum-silicon-lithium sol; the lithium precursor is lithium hydroxide or a lithium-containing alkoxide; the preparation steps of the boron-aluminum-silicon sol include: dissolving an aluminum-containing alkoxide and a siloxane in an aqueous solution of boron oxide or a boron-containing alkoxide and performing a hydrothermal reaction under stirring conditions to obtain the boron-aluminum-silicon sol; the mass ratio of the aluminum-containing alkoxide, the siloxane, and the boron oxide or boron-containing alkoxide is 1:3:4; the mass ratio of the boron-aluminum-silicon sol to the lithium precursor is 5:

2. The preparation steps of the wave-transparent self-cleaning coating material include: adding hydroxyl silicone oil to boron aluminum silicon lithium sol, and then carrying out a hydrothermal reaction under stirring conditions to obtain the wave-transparent self-cleaning coating material.

2. A method for preparing the wave-transparent self-cleaning coating material as described in claim 1, characterized in that, Includes the following steps: Hydroxyl silicone oil is added to boron aluminum silicon lithium sol, and the mixture undergoes a hydrothermal reaction under stirring conditions to obtain the wave-transparent self-cleaning coating material.

3. The application of the wave-transparent self-cleaning material as described in claim 1 in the preparation of organosilicon hydrophobic coatings or microcrystalline glass hydrophilic coatings.

4. A method for preparing an organosilicon hydrophobic coating containing the wave-transparent self-cleaning material of claim 1, characterized in that, Includes the following steps: The microwave-transparent self-cleaning material was ball-milled and then dried to obtain a slurry. The slurry is coated onto the surface of the material and then heat-treated to obtain an organosilicon hydrophobic coating. The drying temperature is 40~80℃; The slurry has a water content of 5%; The heat treatment temperature is 200℃, the heating rate is 5~8℃ / min, and the holding time is 1h.

5. A method for preparing a microcrystalline glass hydrophilic coating containing the wave-transparent self-cleaning material of claim 1, characterized in that, Includes the following steps: The microwave-transparent self-cleaning material was ball-milled and then dried to obtain a slurry. The slurry is coated onto the surface of the material and then heat-treated to obtain an organosilicon hydrophobic coating. The silicone hydrophobic coating is subjected to high-temperature heat treatment to obtain the microcrystalline glass hydrophilic coating. The drying temperature is 40~80℃; The slurry has a water content of 5%; The heat treatment temperature is 200℃, the heating rate is 5~8℃ / min, and the holding time is 1h; The high-temperature heat treatment is performed at a temperature of 700℃, a heating rate of 5~8℃ / min, and a holding time of 1h.

6. A coating prepared by the preparation method according to claim 4 or 5.

Citation Information

Patent Citations

  • Wave-transparent rain-erosion-resistant self-cleaning material and application thereof

    CN116814158A